The Effectiveness of Productive Zakat Program for MSMEs using the Zakat Utilization Index (IPZ) - Fiddareini, Fachrina; Rakhmawati, Rakhmawati (Universitas Siliwangi, 2024)
Introduction to The Problem: Productive zakat has the potential to empower MSMEs. The program's effectiveness needs to be monitored continuously to increase its usefulness. A comprehensive measurement tool to assess the effectiveness of productive zakat is needed. The Zakat Utilization Index (IPZ) by Puskas BAZNAS is one of the tools used to measure the utilization of zakat in five aspects: social, cultural, economic, da'wah, and environmental.Purpose/Objective Study: The article aims to analyze the effectiveness of LAZIS UNISIA’s Gerobak Barokah program in empowering mustahik using the Zakat Utilization Index (IPZ).Design/Methodology/Approach: The study employs a descriptive quantitative approach, using the Zakat Utilization Index (IPZ) to evaluate the effectiveness of the Gerobak Barokah program. The beneficiaries of the Gerobak Barokah are the MSME entrepreneurs in the culinary sector located in Yogyakarta Province. There are 44 mustahik included in data anaysis. Data were collected through 1-5 Likert scale questionnaires based on IPZ Puskas BAZNAS. A multi-stage weighted index was applied to assess five indicators: social, cultural, economic, da'wah, and environmental.Findings: The findings reveal that the Gerobak Barokah program achieved a Zakat Utilization Index (IPZ) value of 0.56, classifying it as